PENANGANAN KHUSUS TERHADAP NARAPIDANA PENDERITA HIV/AIDS BERDASARKAN PERATURAN PEMERINTAH NOMOR 32 TAHUN 1999 TENTANGSYARAT DAN TATA CARA PELAKSANAAN HAK WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KLAS II A PEKANBARU - Yogi Ramadhan Dwiputra; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The condition of prisons in Indonesia are less clean and inadequate to accommodate the number of inmates is very possible the transmission of HIV / AIDS. Which exceeds the capacity of the holding cell can unwittingly transmit HIV / AIDS to the prisoners therein which occurs when blood or sexual contact. Is not new news that in detention cells often occur sex sexual intercourse (sodomy) so in order inmates with HIV / AIDS do not feel discriminated against then those with HIV / AIDS should get proper treatment. Based on Government Regulation No. 32 of 1999 on the terms and procedures for the implementation of the rights of inmates Correctional particular Article 16 (3) mentioned when the results of medical examination of prisoners found infectious diseases or dangerous, then the patient is treated specifically.As for the purpose of writing this essay, namely: First, how special handling of prisoners suffering from HIV / AIDS in Penitentiary Class II A Pekanbaru. Second, obstacles in the process of special handling of prisoners living with HIV / AIDS in Penitentiary Class II A Pekanbaru. Third, the efforts of correctional officers in giving special treatment to inmates suffering from HIV / AIDS in Penitentiary Class II A Pekanbaru.The conclusion that can be derived from this research is the First, implementation of the guidance and treatment for those with HIV / AIDS in Penitentiary Class II A Pekanbaru already well underway, although there are still some obstacles that hinder the implementation of coaching and penanganan.Kedua, Barriers in coaching and handling of prisoners with HIV / AIDS in Lemabaga Penitentiary Class II A Pekanbaru a capacity Penitentiary Class II A Pekanbaru very less in accommodating inmates, Cost to perform medical treatment are minimal, medical personnel is still lacking, especially to handle the problem of HIV / AIDS, medical facilities and infrastructure that is still far from standard. Third, efforts to overcome barriers to the development and treatment of those with HIV / AIDS in correctional Lemabaga Class II A Pekanbaru is as regular coaching berikutMelakukan provide education to prisoners and the prevention of transmission of HIV / AIDS to 12 inmates with HIV / AIDS.Keywords: Handling - Inmates - People with HIV / AIDS SPECIAL HANDLING